Pengembangan Lembar Kerja Peserta Didik Menggunakan Model Problem-Based Learning di Kelas V Sekolah Dasar - Armainia, Nella; Amini, Risda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
The aim of the research is to develop LKPD based on Problem-Based Learning in integrated thematic learning for class V elementary schools. This research is research and development (R&D) with the ADDIE development model with the following stages: analysis, design, development, implementation, and evaluation. The data analysis technique uses expert validation sheets and practicality analysis techniques in the form of teacher and student response questionnaires. Based on the results of the research and discussion, it can be concluded that the development of PBL-based LKPD material in elementary schools is very feasible for use in learning. This is based on the results of the validation of material experts by 95.83%, the results of validation by linguists by 90%, the results of validation by media experts by 91.67% and the results of teacher response questionnaires by 93.75% and students by 93%.